Speed management in rural communities using optical speed bars - Balde, Abdoulaye Diogo (Kansas State University, 2010)
Speed management has been a challenge, particularly in places where high-speed highways pass through. Due to high rate of fatalities and low budgets available, it is therefore necessary to identify low-cost effective approaches in reducing speeds. Optical Speed Bar (OSB) treatment is one such technique. This research makes an attempt to evaluate the effectiveness of OSBs in reducing approach speeds on two-lane, rural highways approaching small communities. Speed data were collected and analyzed “before” and “after” periods at five sites. Effectiveness of OSBs was evaluated using changes in mean and 85th percentile speeds under different categories by considering all vehicles, vehicle classification (two axles vs. more than two axles), day of the week (weekdays vs. weekends), and time of day (daytime vs. nighttime), as well as proportions exceeding posted speed limit, using t-test mean speeds, F-test for analysis of variance, and Z-test for proportions of vehicles exceeding posted speed limit between “before” and “after” datasets. Even though motorists were found to slow down on the approaches, in response to speed zones, speeding was noted. “Before” speed data indicated higher speeds than desired at the sites. The 85th percentile speeds were between 50 and 63 mph while the posted speed limits on the approaches were 45 mph at four sites, and the 85th percentile speed was about 42 mph at one site with an approach posted speed limit of 30 mph. The “before” degrees of noncompliance were up to 90 % of free-flowing vehicles at the sites. Speed data analysis showed significant reductions in speeds at ends of OSBs at four test sites. Mean and 85th percentile speeds and standard deviations were found reduced in the after periods. Percent reductions in mean speeds were between 1.2 and 8.2 %, with 85th percentile reductions between 3.2 and 8.9 %. At one site, no notable change in mean and 85th percentile speeds occurred at the end of OSBs, but significant increases in standard deviations were noted. Speed reductions were higher for two-axle vehicles, during the daytime and on weekdays with few exceptions. Results of the study showed, as other previous studies did, OSBs may have some minor effects on vehicle speeds. The study provides an indication that it may be possible to create safety improvements as result of using OSBs on the approach to a rural community. However, magnitude of speed reductions was generally small, though the reductions were statistically significant at the 95% confidence level. Because of the non-consistence of the magnitude of speed reductions at the test sites, no conclusion can be drawn as to how much OSB treatment reduced speeds. These results were based on “after” periods up to five months. Therefore, further study would be required to determine whether these safety improvements are sustained over an even longer time period. Even though minor speed reductions occurred, speeds observed at the sites were still higher than the posted speed limits, indicating OSBs were not effective enough in providing the desired speed limit compliance. Additional studies would be helpful to identify combinations of countermeasures, for instance OSBs and other techniques, effective in providing speed limit compliance.
Keywords: Speed management in rural communities; Optical speed bars; Engineering, Civil (0543)